Anti-tumoral Effects of Recombinant Lactococcus lactis Strain Secreting IL-17A Cytokine - Jacouton, Elsa; Torres Maravilla, Edgar; Boucard, Anne-Sophie; Pouderous, Nicolas; Pessoa Vilela, Ana Paula; Naas, Isabelle; Chain, Florian; Azevedo, Vasco; Langella, Philippe; Bermúdez-Humarán, Luis G. (Frontiers in Microbiology, 2019)
Interleukin-17A (IL-17A) is a pro-inflammatory cytokine produced by TH17 cells that participates and contributes in host defense and autoimmune disease. We have recently reported antitumor properties of the probiotic strain of Lactobacillus casei BL23 in mice and TH17 cells was shown to play an important role in this beneficial effect. In order to better understand the role of IL-17A in cancer, we constructed a recombinant strain of Lactococcus lactis producing this cytokine and we determined its biological activity in: i) a bioassay test for the induction of IL-6 production by murine fibroblasts 3T3 L1 cells line and then ii) in the TC-1 mouse allograft model of human papilloma virus (HPV)-induced cancer. Our data show that recombinant L. lactis can produce and efficiently secrete biologically active IL-17A cytokine. Interestingly, ~26% of mice intranasally treated with L. lactis-IL-17A and challenged with TC-1 cells remained tumor free over the experiment, in contrast to control mice treated with the wild type strain of L. lactis which developed 100% of aggressive tumors. In addition, the median size of the ~74% tumor-bearing mice treated with recombinant L. lactis-IL-17A, was significantly lower than mice treated with wt-L. lactis. Altogether, our results demonstrate that intranasal administration with L. lactis secreting IL-17A results in a partial protection against TC-1-induced tumors in mice, confirming antitumor effects of this cytokine in our cancer model.